Human beings and dolls in oriental philosophy of life (based on japanese literature and cinema) (Eurasian Journal of Philology Science and Education, 2018)
This article focuses on cultural, aesthetic, and philosophical aspects of the art of dolls. The subject of analysis is metaphorical and symbolic meaning of a doll in the art of the East, namely, in the Japanese art (theater, literature, and cinema). Particular attention is given to analysis of the plot and implementation of the Takeshi Kitano’s move «Dolls» and literature of Ryūnosuke Akutagawa. It is noted that Kitano and Akutagawa expressed in the form of artistic expression (cinema and literature) a number of ethical and philosophical and psychological issues of self-consciousness, love and death, freedom and destiny. The article highlights the most significant aspects of the dialectical interrelationship and interdependence of the human and puppet worlds.